2006
DOI: 10.1021/jm060485n
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Uridine 5‘-Diphosphate Analogues at the Human P2Y6 Receptor

Abstract: The structure-activity relationships and molecular modeling of the uracil nucleotide activated P2Y6 receptor have been studied. Uridine 5'-diphosphate (UDP) analogues bearing substitutions of the ribose moiety, the uracil ring, and the diphosphate group were synthesized and assayed for activity at the human P2Y6 receptor. The uracil ring was modified at the 4 position, with the synthesis of 4-substituted-thiouridine 5'-diphosphate analogues, as well as at positions 2, 3, and 5. The effect of modifications at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 42 publications
2
81
0
Order By: Relevance
“…Potential agonist activities of the UDP analogs, UDP␤S (Malmsjö et al, 2000) and 2-thio-UDP (Besada et al, 2006) also were examined in P2Y 14 -HEK293 cells. As is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential agonist activities of the UDP analogs, UDP␤S (Malmsjö et al, 2000) and 2-thio-UDP (Besada et al, 2006) also were examined in P2Y 14 -HEK293 cells. As is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 H]inositol phosphate accumulation in 1321N1 human astrocytoma cells as described previously (Besada et al, 2006). MAP Kinase Activation Assays.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Müller and coworkers and Besada et al reported that certain 5′-triphosphate derivatives potently activate the P2Y 6 receptor. 4,5 The conformational preference of the ribose moiety in binding to uridine nucleotide-activated P2Y receptors has been explored through substitution with the sterically constrained methanocarba (bicyclo[3.1.0]hexane) ring nucleotides also were prepared by the one-pot method using a sequential reaction of 49 and 50 with phosphorus oxychloride and pyrophosphoric acid tributylammonium salt, but the yields were lower.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Tocris introduced the UDP-based selective P2Y 6 agonist PSB 0474 (26) [35]. The elucidation of a 5-iodo-UDP, MRS 2693 (27), provided a potent and selective agonist at the human P2Y 6 receptor, demonstrating an EC 50 value of 15 nM in vitro and no activity at other P2Y subtypes [36]. This compound contains a large phenylacyl substituent which enhances its selectivity for P2Y 6 over P2Y 2 and P2Y 4 which may also be activated by UDP derivatives.…”
Section: Adp Atp and Udp Mimeticsmentioning
confidence: 99%